Military jets - Winchester, Jim (Amber Books, 2019)
Illustrated with detailed artworks and color photographs, Military Jets is a comprehensive study of key air superiority and ground attack aircraft developed since World War II. This essential guide to all the most important jet fighter aircraft from 1945 to the present is a must-have for aviation enthusiasts and modelers. Arranged chronologically, each plane has a cutaway artwork labeled with key items of interest, and accompanying photographs showing both the aircraft's cockpit and exterior from every angle. All the major types, including the Phantom II, MiG-21, and F-22 Raptor, appear with detailed specifications.